Post-Procedural Outcomes in Subarachnoid Hemorrhage Patients Following Endovascular Coiling for Aneurysm Rupture at Dr. Moewardi General Hospital, Surakarta, Indonesia - Shafira Nur Hanifa; Subandi (Magna Neurologica, 2025)
Background: The insidious event of a ruptured intracranial aneurysm (IA) poses the requirement for urgent and effective medical intervention. Endovascular coiling came as an efficacious treatment option. However, no conclusive guideline is available regarding the best time to perform endovascular coiling on the ruptured IA. Objective: The study aims to evaluate the association of timing with endovascular coiling treatment and the post-procedural outcome. Methods: A retrospective cohort study was conducted on a Subarachnoid Hemorrhage (SAH) patient who underwent endovascular coiling on Dr. Moewardi General Hospital, Surakarta, Indonesia, between January 2021 and December 2023. The association between time to endovascular coiling and the postoperative outcome (evaluated by hospitalization duration, modified Rankin Score/mRS, and mortality) was assessed. Results: Of the 50 patients included in the study, it was observed that the aneurysms treated varied in size from 3.1 to 13 mm, with the internal carotid artery being the most common location. The analysis revealed that early intervention, performed within the first 3 days after rupture, significantly reduced the length of hospital stay compared to delayed intervention (6.467 vs. 8.80 days, p <0.030) and resulted in better functional outcome, evaluated by mRS (p <0.003). Despite the positive outcomes, the study also reported a postoperative mortality incidence in three patients. Conclusion: Earlier endovascular coiling in SAH patients can lead to shorter hospitalization and improved functional outcomes, highlighting the importance of timely intervention in managing this critical condition.